Analisa Kualitas Lingkungan Udara Ambien (PM2.5) di Kota Surabaya - Dea Kirana Nurlaili; Novirina Hendrasarie (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Particulate pollution increases with population and activity. Likewise, the city of Surabaya is the 2nd largest metropolitan city in Indonesia based on its population. PM2.5 is a fine particulate that can pose a greater health risk than PM10. This research aims to identify PM2.5 ambient air quality in the city of Surabaya by analyzing daily fluctuations in PM2.5 and calculating an index to be able to categorize ambient air quality in the city of Surabaya. The analytical method used is a quantitative observation method that involves analyzing fluctuations in the distribution of PM2.5 over 24 hours and 7 days and calculating ISPU and NAAQS. The results of the observations showed an increase in PM2.5 particulates at certain times, and the highest spike in PM2.5 levels occurred on Saturday. Based on ISPU and NAAQS calculations, there are differences: according to ISPU, the ambient air quality in Surabaya is classified as moderate, while according to US-EPA standards, the ambient air quality in Surabaya is classified as unhealthy for sensitive groups.